'Learning the Ropes' in a Psychologically Safe Healthcare Environment - Lishin Joshy (ACHSM, 2024)
Objectives: The main objective of the study is to examine the associations between organizational socialization, psychological safety and job involvement of newly hired nursing professionals in India through the lens of 'Conservation of resources theory'. The study also explored psychological safety as a mechanism linking organizational socialization and job involvement. Design/Methodology: Data was collected from 286 Indian nursing professionals who recently joined their respective organizations. The cross-sectional data was analyzed using IBM SPSS and POCESS macro model 4. Outcomes: The results reveal that organizational socialization is positively associated with nursing professionals' job involvement, and that this relationship is mediated by feelings of psychological safety. Conclusions: Healthcare organizations can translate the findings into organizational advantages by institutionalizing organizational socialization and thereby increasing job involvement. It was identified that nursing professionals who have undergone organizational socialization processes experience psychological safety, and that it is the latter that is the link between organizational socialization and job-involvement.